IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN KUALITAS TENAGA PENDIDIK DI MADRASAH ALIYAH TERPADU AL-ANWAR DURENAN TRENGGALEK - Sakti, Nadiya Fadhila (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to: (1) describe the planning of educator resource management in Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek. (2) Describe the implementation of educator resource management at the Integrated Madrasah Aliyah Al-Anwar Durenan Trenggalek. (3) Describe the efforts of the head of the madrasa in improving the quality of educators at the Al-Anwar Integrated Madrasah Al-Anwar Durenan Trenggalek. The type of research used in this research is field research with a qualitative descriptive approach. The data processed were the results of interviews with informants, namely the Principal and Teachers at the Al-Anwar Integrated Madrasah Al-Anwar Durenan Trenggalek. Data collection techniques used are by conducting observations, interviews, and documentation. Meanwhile, the data analysis technique was carried out by means of data reduction, data presentation, verification and drawing conclusions. The results showed that the human resources at Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek could be categorized as good or adequate both in quantity and quality. The implementation of human resource management in improving the quality of educators at Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek has been carried out well, especially in terms of: HR placement, HR training and development, performance appraisal using qualitative and quantitative assessments, as well as compensation/payment of incentives. Efforts to improve the quality of educators at Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek have been carried out well in terms of understanding the demands of the profession, achieving qualifications and competencies, building good and broad peer relations through professional organizations, developing work ethic, and adopting innovations in the use of communication and information technology. Keywords: Human Resource Management and Quality of Educators. ABSTRAK Penelitian ini bertujuan untuk: (1) Mendeskripsikan perencanaan manajemen sumber daya pendidik di Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek. (2) Menggambarkan implementasi manajemen sumber daya pendidik di Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek. (3) Mendeskripsikan upaya kepala madrasah dalam peningkatan kualitas tenaga pendidik di Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek. Jenis penelitian yang digunakan dalam penelitian adalah field research dengan pendekatan deskriptif kualitatif. Data yang diolah adalah hasil wawancara dari informan yaitu Kepala Madrasah dan Tenaga Pendidik pada Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek. Teknik pengumpulan data yang digunakan yaitu dengan melakukan observasi, wawancara, dan dokumentasi. Sedangkan teknik analisis data dilakukan dengan cara reduksi data, penyajian data, verifikasi dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa sumber daya manusia di Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek dapat di kategorikan baik atau memadai baik kuantitas maupun kualitas. Implementasi manajemen sumber daya manusia dalam meningkatkan kualitas tenaga pendidik di Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek sudah dilaksanakan dengan baik terutama dalam hal: penempatan SDM, pelatihan dan pengembangan SDM, penilaian kinerja menggunakan penilaian kualitatif dan kuantitatif, serta kompensasi/pemberian honor insentif. Upaya dalam meningkatkan kualitas tenaga pendidi di Madrasah Aliyah Terpadu Al-Anwar Durenan Trenggalek sudah dilakukan dengan baik dalam hal memahami tuntutan profesi, mencapai kualifikasi dan kompetensi, membangun hubungan kesejawatan yang baik dan luas melalui organisasi profesi, mengembangkan etos kerja, dan mengadopsi inovasi dalam pemanfaatan teknologi komunikasi dan informasi. Kata kunci: Manajemen Sumber Daya Manusia dan Kualitas Tenaga Pendidik.